Reappraisal of Synagrops Günther, 1887 with rehabilitation and revision of Parascombrops Alcock, 1889 including description of seven new species and two new genera (Perciformes: Acropomatidae) - Schwarzhans, Werner W.; Prokofiev, Artem M. (Zootaxa, 2017)
An ongoing review of the fishes of the basal percoid family Acropomatidae has revealed that the genus Synagrops Günther, 1887 as it is currently understood is not a natural group. Species with a serrated pelvic-fin spine are here placed in the resurrected genus Parascombrops Alcock, 1889 (type-species: Parascombrops pellucidus Alcock, 1889), and the new, monospecific genus Caraibops n. gen. (type-species: Synagrops trispinosus Mochizuki & Sano, 1984). Parascombrops is unique amongst Acropomatidae in the combination of the presence of vacant 8th interneural space, a predorsal formula /0+0/0+2/ and an epaxialis attachment type 1. Caraibops n. gen. shares none of these characters and further differs from Parascombrops by an anal-fin formula of III + 9 (vs II + 7 or III + 6), and the absence of denticles on the ectopterygoid. Parascombrops is revised and now contains a total of 13 species, including 7 new: P. analis (Katayama, 1957), P. argyreus (Gilbert & Cramer, 1897), P. glossodon n. sp., P. madagascariensis n. sp., P. mochizukii n. sp., P. nakayamai n. sp., P. ohei n. sp., P. parvidens n. sp., P. pellucidus Alcock, 1889, P. philippinensis (Günther, 1880), P. serratospinosus (Smith & Radcliffe, 1912), P. spinosus (Schultz, 1940) and P. yamanouei n. sp. Synagrops adeni Kotthaus, 1970 and S. malayanus Weber, 1913 are treated as synonyms of P. pellucidus and P. philippinensis, respectively. Lectotypes are designated for P. philippinensis and S. malayanus. The main characters used to distinguish between the species of Parascombrops are: serration of other fin spines, number of gill rakers and pseudobranchial filaments, head profile, presence or absence of ridges on the preopercle, shape of 1st anal-fin pterygiophore, dentition on vomer, palatines and ectopterygoids, orbit diameter, pectoral-fin length, maximal body depth and otolith morphology. The genus Synagrops is here confined to two species, S. japonicus (Döderlein, 1883) and S. bellus (Goode & Bean, 1896), characterized by the apomorphic character of an otic capsule with a posteriorly open myodome, a basioccipital fossa and a very specialized otolith morphology. Synagrops is also characterized by the absence of pelvic-fin spine serrations. Two other species without a serrated pelvic-fin spine, originally described in Synagrops, are removed from this genus. Synagrops microlepis Norman, 1935 is separated into the monotypic Kaperangus n. gen., the only genus in the family with two supraneurals (cf. three in all other taxa). The second, Synagrops pseudomicrolepis Schultz, 1940 is re-assigned to the genus Verilus. The geographic distribution of Parascombrops as currently composed is discussed, and is shown to be primarily of West Pacific nature, with few species in the Indian Ocean and one in the tropical West-Atlantic (P. spinosus). The West Atlantic species Parascombrops spinosus is very closely related to P. mochizukii from the tropical northwestern Pacific, and the implications of this disjunct distribution are discussed. The high degree of speciation now recognized in Parascombrops species of the West-Pacific indicates that a diverse ecological adaptation within an overall pseudoceanic habitat may have played a major role in speciation, which would have remained obscured without adequate taxonomic resolution. Fossil, otolith-based records are also briefly discussed in the context. The extant Parascombrops argyreus and P. ohei are reported from the Pliocene of Japan, and Caraibops trispinosus has been recorded from the Pliocene of Venezuela.